#TITLE_ALTERNATIVE# - MUSTIKA WIDARTININGSIH (NIM : 10210080); Pembimbing : Dr. rer. nat. Sparisoma Viridi; Dr.Eng. , PUTRI
This final project presents an analytical study of the correlation between viscosity and fiber diameter in electrospinning. Controlling fiber diameter during electrospinning process was important since it will determine the performance of resulting nanofiber. Theoretically, fiber diameter was determined by surface tension, solution concentration, flow rate, and electric current. But experimentally it had been proven that significantly viscosity had an influence to fiber diameter. Jet radius equation in electrospinning process was divided into three areas: near the nozzle, far from the nozzle, and terminal diameter of the whipping jet. The role of viscosity greatly determining jet diameter near the nozzle. There was no correlation between these equations. Superposition of exponential series model provides the equations combined into one. Thus the entire of working parameters on electrospinning took a contribution to fiber diameter. This model yields the value of solution viscosity has a linear relation to the jet radius. To determine the correlation between fiber diameter and jet radius, carried out by empirical analysis using the number of experimental data from various references.